Current Updates on Molecular Diagnostic Assays Used for Detection of Candida auris: A Systematic Review - River Chun-Wai Wong; Alfred Lok-Hang Lee; Ingrid Yu-Ying Cheung; Viola Chi-Ying Chow; Margaret Ip; Christopher Koon-Chi Lai (Diagnostics)
Background/Objectives: Candida auris is an emerging multidrug-resistant pathogen with the potential to cause invasive fungal infections and healthcare-associated outbreaks. Currently, there is no systematic review explicitly focusing on the up-to-date molecular diagnostics of this pathogen to cover the entire process, including sample pre-extraction procedures, nucleic acid extraction, and DNA-based detection. Sample pre-treatment and extraction are the prerequisites before molecular testing and have implications on the downstream detection but have not been reviewed elsewhere. This review aims to summarize a comprehensive update in the past 5 years. Methods: A systematic review was conducted to search for articles published in the period between 1 January 2020 and 20 November 2024 from various databases, including PubMed, Google Scholar, and Web of Science. The findings were produced through narrative synthesis, with quantitative analysis conducted where applicable. Results: Starting from 1115 records, 28 studies that met the inclusion criteria were included in the analysis. This review summarized the key updates on three categories, including (i) sample pre-extraction procedures and nucleic acid extraction, including magnetic, bead-beating, mechanical, chemical, thermal, and column-based protocols; (ii) commercial molecular assays; and (iii) laboratory-developed tests (LDTs). For real-time PCR, commercial molecular assays and LDTs showed sensitivity (ranging from 94.9% to 100% and 44% to 100%, respectively) and specificity (ranging from 98.2% to 100% and 92% to 100%, respectively). Conclusions: Here, we describe a useful summary to enlighten readers from clinical microbiology laboratories on the nucleic acid extraction protocols and performance of various molecular diagnostic assays used for the detection of C. auris.